PENGARUH PERSPEKTIF PEMBELAJARAN DAN PERTUMBUHAN TERHADAP KINERJA PERUSAHAAN DENGAN PENDEKATAN BALANCED SCORECARD (STUDI KASUS PT PERMATA HIJAU PALM OLEO KIM II) - Soeseny, Rury Erna; Yahya, M. Rizal; Haridhi, Musfiari (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
The purpose of this study is to determine the ability of employees; information system capabilities; motivation, empowerment, and alignment; and learning and growth perspectives have an effect on company performance using theapproach balanced scorecard. This research uses descriptive quantitative research. The results showed that the abilities of the employees; information system capabilities; motivation, empowerment, and alignment; and learning and growth perspectives have an effect on company performance using theapproach balanced scorecard.